PEMANFAATAN FINANCIAL TECHNOLOGY PADA UMKM DI KECAMATAN TEMBALANG - Pramuditha Dwi Firmansyah; Sulartopo, Sulartopo; Kusumajaya, Robby Andika (MANAJEMEN, 2024)
The role of the financial sector in the economy is very large and continues to grow to meet people's needs. Financial technology or (fintech) is a term used to describe innovation that occurs in the financial sector. The use of financial technology in micro, small and medium enterprises (MSMEs) in Tembalang District aims to measure how the application of financial technology has an impact on the growth and competitiveness of MSMEs in the area. This research involves a survey of a number of small and medium enterprises (MSMEs) that have adopted various fintech services, such as technology-based financial management and digital payments. This research was conducted to identify changes in operational efficiency, access to capital, and competitiveness of MSMEs in Tembalang District. The results of this research are expected to provide an in-depth picture of the extent to which the use of fintech has supported the growth and demand of MSMEs in Tembalang District as well as provide policy recommendations to increase the role of fintech in supporting the MSME sector.